Thermal grill illusion of pain in patients with chronic pain: a clinical marker of central sensitization?. Issue 3 (15th March 2023) - Adam, Frédéric; Jouët, Pauline; Sabaté, Jean-Marc; Perrot, Serge; Franchisseur, Claire; Attal, Nadine; Bouhassira, Didier
Abstract : The thermal grill illusion of pain is significantly increased in patients with fibromyalgia or irritable bowel syndrome. Abstract: The thermal grill illusion of pain (TGIP) is a paradoxical burning pain sensation elicited by the simultaneous application of innocuous cutaneous warm and cold stimuli with a thermode ("thermal grill") consisting of interlaced heated and cooled bars. Its neurophysiological mechanisms are unclear, but TGIP may have some mechanisms in common with pathological pain, including central sensitization in particular, through the involvement of N-methyl-d -aspartate receptors. However, few studies have investigated TGIP in patients with chronic pain and its clinical relevance is uncertain. We hypothesized that the TGIP would be increased in comparison with controls in patients with fibromyalgia or irritable bowel syndrome, which are regarded as typical "nociplastic" primary pain syndromes related to changes in central pain processing. We compared the sensations elicited by a large range of combinations of temperature differentials between the warm and cold bars of a thermal grill applied to the hand between patients with fibromyalgia (n = 30) or irritable bowel syndrome (n= 30) and controls (n = 30). The percentage of TGIP responses and the intensity and unpleasantness of TGIP were significantly greater in patients than controls. Furthermore, positive correlations were found between TGIP intensity and clinical pain intensity and between TGIP intensity and the cold pain threshold measured on the hand. These results are consistent with our working hypothesis of shared mechanisms between TGIP and clinical pain mechanisms in patients with nociplastic chronic pain syndromes and suggest that TGIP might represent a clinical marker of central sensitization in these patients.